Get in the Flow: A Descriptive Qualitative Study to Investigate Educational Video Games Inside Pre-K to 5th Grade Classrooms - Hill, Aaron (My University, 2025)
This study was a descriptive investigation of early childhood educators’ perceptions of educational video game-based learning in the classroom. The research questions included: (a) What are early childhood educators’ perceptions of learning gains after implementing video game-based learning in the classroom? (b) What are the experiences of elementary school educators implementing video game-based learning? and (c) How can teachers effectively incorporate video game-based learning into the curriculum? The participants were five educators from multiple school districts in the southeastern region of the United States. Data collection involved classroom observations and interviews, which were recorded, transcribed, and analyzed to capture the perceptions of educators utilizing video game-based learning strategies in the classroom. Educators who employ video game-based learning must be properly trained in implementing educational games into both the classroom and the curriculum. Six common themes emerged from the findings regarding educators' perceptions of educational video game-based learning: (a) flow and engagement, (b) relaxation and the learning environment, (c) focus and concentration, (d) excitement and motivation, (e) behavior and classroom management, and (f) fun and educational value. The data from this study will be instrumental in helping educators enhance academic achievement through the use of educational video games in school settings.
Keywords: Dissertations, Academic--United States; Education; Educational games; Early childhood education; Elementary school teachers; Educational technology; Classroom management; Art teachers--Attitudes; Video games; Learning; Southern States